Family ties strengthening the family unit - Friedman, Gayle; Friedman, Gayle; S. Weber, Amy (New Jersey : Meridian Education Corporation, 2000)
This program offers ways in which families can begin to build a cohesive bond by celebrating their uniqueness and learning how a little bit of hard work can create a positive and loving environment that's benefical to every member.
Copy available in DVD format
Executive producer, Twila Sears and Amy S. Weber ; editor, Jodi Gonska
Keywords: Family; Relationship between parent and adult child